Implementasi kurikukum merdeka belajar di SMK Pusat Keunggulan - Nanang Setiawan; Herminarto Sofyan (Universitas Sarjanawiyata Tamansiswa, 2022)
The independent learning curriculum is a prototype curriculum that has currently been implemented in 2500 activator schools and 901 SMK Centers of Excellence (SMK PK). This study aims to describe the findings of scientific journal articles regarding the implementation of the independent learning curriculum at SMK PK through a literature review. This research is expected to be a reference and consideration for policymakers to make improvements and socialization to other vocational schools so that they can implement the independent learning curriculum well and efficiently. Searching for research journal data using a database from Google Scholar by applying the keywords